2013
DOI: 10.1039/c2ee23635d
|View full text |Cite
|
Sign up to set email alerts
|

Transparent and conductive paper from nanocellulose fibers

Abstract: Here we report on a novel substrate, nanopaper, made of cellulose nanofibrils, an earth abundant material.Compared with regular paper substrates, nanopaper shows superior optical properties. We have carried out the first study on the optical properties of nanopaper substrates. Since the size of the nanofibrils is much less than the wavelength of visible light, nanopaper is highly transparent with large light scattering in the forward direction. Successful depositions of transparent and conductive materials inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
362
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 461 publications
(367 citation statements)
references
References 28 publications
4
362
1
Order By: Relevance
“…Hu et al (2013) showed that nanocellulose films could be rendered conductive by deposition of tindoped indium oxide, while still retaining their transparency; solar cells prepared with such films were successfully demonstrated. In general, it has been found that good transparency can be achieved as long as the cellulosic material is small enough, fully wetted by the matrix material (if any) in the layer, and not clumped up or entangled.…”
Section: Transparencymentioning
confidence: 96%
See 3 more Smart Citations
“…Hu et al (2013) showed that nanocellulose films could be rendered conductive by deposition of tindoped indium oxide, while still retaining their transparency; solar cells prepared with such films were successfully demonstrated. In general, it has been found that good transparency can be achieved as long as the cellulosic material is small enough, fully wetted by the matrix material (if any) in the layer, and not clumped up or entangled.…”
Section: Transparencymentioning
confidence: 96%
“…A number of researchers have demonstrated such a process when using nano-fibrillated cellulose (Nakagaito and Yano 2004Henriksson et al 2008;Nogi et al 2009;Syverud and Stenius 2009;Sehaqui et al 2010Sehaqui et al , 2011Larsson et al 2012;Hu et al 2013;Rojo et al 2015). Keshvarzi et al (2015) prepared paper-like films from a gelled mixture of nanocellulose and zeolites.…”
Section: Filtration and Papermaking Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanocellulose (NFC) has gained considerable attention in recent years due to its outstanding mechanical and chemical properties [9,10], especially when used in composites [11,12]. Nanocellulose used in paper form, herein termed nanopapers, possesses excellent mechanical properties, low thermal expansion coefficients, high optical transparency and good gas barrier properties [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%